2018
DOI: 10.3390/ma11101850
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical Properties and Tribological Properties of NiAlComposites Reinforced by CrMnFeCoNiHigh-Entropy Alloy

Abstract: NiAl-based composites reinforced by CrMnFeCoNi high-entropy alloy (HEA) particles were fabricated by mechanical alloying (MA) and spark plasma sintering (SPS). The microstructure, mechanical, and tribological properties of the NiAl-HEA composites were investigated. Microstructural analyses show that after SPS, the HEA phase homogenously distributed in the NiAl matrix. Non-uniform diffusion of various elements occurred during the high temperature sintering process. Transmission electron microscope (TEM) observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Even in some cases, a little intermetallic compounds precipitate in the single solid solution matrix, leading to the further enhancement of the mechanical properties of HEAs [ 3 , 5 ]. Additionally, recent studies have shown that the HEAs fabricated using different methods exhibit superior mechanical and physical properties such as high hardness, ultrahigh fracture toughness, good wear resistance, good tribological properties, excellent high temperature softening resistance, good magnetic properties, and good corrosion resistance [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. It has been claimed that these promising properties are ascribed to the high-entropy of alloys, the sluggish diffusion, the cocktail effect, and the large lattice distortion of the respective structures [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 12 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even in some cases, a little intermetallic compounds precipitate in the single solid solution matrix, leading to the further enhancement of the mechanical properties of HEAs [ 3 , 5 ]. Additionally, recent studies have shown that the HEAs fabricated using different methods exhibit superior mechanical and physical properties such as high hardness, ultrahigh fracture toughness, good wear resistance, good tribological properties, excellent high temperature softening resistance, good magnetic properties, and good corrosion resistance [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. It has been claimed that these promising properties are ascribed to the high-entropy of alloys, the sluggish diffusion, the cocktail effect, and the large lattice distortion of the respective structures [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 12 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%